Lens nuclear opacity quantitation with long-range swept-source optical coherence tomography: correlation to LOCS III and a Scheimpflug imaging-based grading system. Issue 8 (12th October 2018) - Chen, Ding; Li, Zhangliang; Huang, Jinhai; Yu, Liuqing; Liu, Songjia; Zhao, Yun-e
Abstract : Purpose: To quantitate lens nuclear opacity using long-range swept-source optical coherence tomography (SS-OCT) images and to evaluate the correlation of this method to Lens Opacities Classification System III (LOCS III) and a Scheimpflug imaging-based grading system (Pentacam Nuclear Stage function; PNS). Methods: This study enrolled 120 participants (120 eyes) with age-related nuclear cataracts. The best-corrected visual acuity (BCVA), LOCS III nuclear opalescence (NO) and nuclear colour (NC) were obtained. The nuclear density measured using PNS function (NDPNS ) was recorded. Three successive series of long-range SS-OCT images were captured, and the nuclear region was analysed using ImageJ (NIH, Bethesda, Maryland, USA) to generate SS-OCT image-based nuclear density (NDSS-OCT ). The repeatability of NDSS-OCT measurement was evaluated using within-subject coefficient of variation (CVw ) and intraclass correlation coefficient (ICC). Correlations of NDSS-OCT with NO and NC, BCVA and NDPNS were analysed. According to the integrity of nucleus imaged by Pentacam, patients were divided into two groups, and the parameters were compared between groups. Results: The CVw and ICC for NDSS-OCT measurement were 1.5 % and 0.994, respectively. The NDSS-OCT significantly correlated with NO (r=0.831), NC (r=0.873), BCVA (r=0.655) and NDPNS (r=0.891). The NDSS-OCT, NO and NC, and BCVA were significantly different between the two groups. Conclusion: Lens nuclear opacity quantitation using long-range SS-OCT images was repeatable and correlated well with LOCS III and PNS function. The Scheimpflug principle had a limitation in imaging dense nucleus. Long-range SS-OCT seems more promising for objectively and quantitatively assessing lens nuclear opacity.